2019
DOI: 10.1111/sji.12820
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of epithelial‐derived mediators and interleukin‐4/interleukin‐13 signaling after bronchial challenge with Dermatophagoides pteronyssinus in patients with allergic asthma

Abstract: Allergens are the main trigger that enhances airway type 2 inflammation, and the epithelium is the first line of defense that reacts to its exposure. Therefore, epithelial‐derived mediators, such as interleukin (IL)‐25, IL‐33, thymic stromal lymphopoietin (TSLP) and ezrin, may play a role as alarmins in IL‐4/IL‐13 signaling in allergic asthma (AA). We investigated the serum levels of IL‐25, IL‐33, TSLP, ezrin, IL‐4 and IL‐13, after bronchial challenge with Dermatophagoides pteronyssinus in patients with AA. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 49 publications
4
19
1
Order By: Relevance
“…Peripheral eosinophil counts were particularly high in this study and as for IL-13, peripheral eosinophilia was also correlated with disease severity. Kalinauskaite-Zukauske et al reported a significantly higher IL-13 levels in atopic asthma patients compared to the control group and an increase in IL-13 levels after bronchial allergen challenge test with D. pteronyssinus (18). Basal peripheral eosinophil counts were nearly twice the control group in atopic asthmatic patients in this study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Peripheral eosinophil counts were particularly high in this study and as for IL-13, peripheral eosinophilia was also correlated with disease severity. Kalinauskaite-Zukauske et al reported a significantly higher IL-13 levels in atopic asthma patients compared to the control group and an increase in IL-13 levels after bronchial allergen challenge test with D. pteronyssinus (18). Basal peripheral eosinophil counts were nearly twice the control group in atopic asthmatic patients in this study.…”
Section: Discussionsupporting
confidence: 55%
“…The authors also stated that there was no difference in these two cytokines when controlled and uncontrolled asthma patients were compared. In another study, where baseline IL-25 and TSLP levels were similar between atopic asthmatic patients and control group, a significant increase in these two cytokine levels was observed after bronchial inhaler challenge (18). In our study, IL-25 and TSLP was not detected in the serum of phenotype 2 patients in which none of the patients were under long term systemic steroid therapy.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…91 In contrast, acute bronchial challenge of patients with steroidnaïve mild allergic asthma with Dermatophagoides pteronyssinus resulted in enhanced serum levels of ezrin and IL-13 after 24 hours. 92 The authors suggested that acute asthma attacks result in heightened release of biologically active substances such as ezrin from damaged AECs, which initiates an IL-13-driven immune cascade that results in further increases in ezrin levels. 92 Further studies are required to look at temporal changes in ezrin levels in various biosamples and the impact of natural asthma exacerbations.…”
Section: Emerging Biomarkersmentioning
confidence: 99%
“…92 The authors suggested that acute asthma attacks result in heightened release of biologically active substances such as ezrin from damaged AECs, which initiates an IL-13-driven immune cascade that results in further increases in ezrin levels. 92 Further studies are required to look at temporal changes in ezrin levels in various biosamples and the impact of natural asthma exacerbations. Chitinase-3-like protein 1 (CHI3L1), also known as YKL40, is expressed and secreted by various cells such as epithelial cells, macrophages, neutrophils and smooth muscle cells.…”
Section: Emerging Biomarkersmentioning
confidence: 99%